HUBUNGAN KOMUNIKASI INTERNAL DENGAN MOTIVASI BELAJAR DALAM KELOMPOK BELAJAR SISWA KELAS VIII SMPN 3 PADALARANG - Maya Masyita Suherman (Jurnal Selaras : Kajian Bimbingan dan Konseling serta Psikologi Pendidikan, 2021)
The purpose of this study was to determine the relationship between internal communication and learning motivation of students at SMPN 3 Padalarang. The approach used in this research is a quantitative approach with a correlational method. The research sample consisted of 52 students from class VIII. Data collection tools in this study used an internal communication scale (38 items; α = 0.863) and a learning motivation scale (29 items; α = 0.763). Based on the data analysis, the results of the research on the relationship between learning motivation and internal communication obtained the sig value. (2-tailed) Pearson correlation of 0.808, which means that there is a very strong positive relationship, which means that internal communication in the study group can be used as a predictor of student learning motivation in the classroom. Students with high internal communication in study groups can be predicted to have high learning motivation as well, on the other hand, internal communication in low student study groups can be predicted that these students have low learning motivation. Keyword: : internal communication, learning motivation, students